CADAR DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Dahliati Simanjuntak (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2022)
In this regard, the veil has become a very controversial issue in Islam. Some Muslims regard it as a command of Allah contained in the Qur'an, while other Muslims and non-Muslims, especially Westerners, the veil is identified as clothing that comes from Arab culture, many people assume that the wearing of the veil judged as excessive clothing and people who wear it are considered to shut themselves off from social interaction, and it is feared that there will be misuse of the veil for bad interests. Many Muslims argue that whatever the justification for the purdah (ie, veil) in the past, it has no relevance at all to modern times. The orthodox Muslim community, especially the ulama, on the other hand considers the veil for women as an absolute necessity, with its use becoming a habit.